2013
DOI: 10.1063/1.4794081
|View full text |Cite
|
Sign up to set email alerts
|

GaN-based high contrast grating surface-emitting lasers

Abstract: GaN-based high contrast grating surface-emitting lasers (HCG SELs) with AlN/GaN distributed Bragg reflectors were reported. The device exhibited a low threshold pumping energy density of about 0.56 mJ/cm2 and the lasing wavelength was at 393.6 nm with a high degree of polarization of 73% at room temperature. The specific lasing mode and polarization characterisitcs agreed well with the theoretical modeling. The low threshold characteristics of our GaN-based HCG SELs faciliated by the Fano resonance can serve a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…By a careful design, large field enhancement can occur either in the air gap or the grating bar. This opens up various applications such as sensing [35] or surface emitting laser [36]. …”
Section: Crossings and Anti-crossingsmentioning
confidence: 99%
See 1 more Smart Citation
“…By a careful design, large field enhancement can occur either in the air gap or the grating bar. This opens up various applications such as sensing [35] or surface emitting laser [36]. …”
Section: Crossings and Anti-crossingsmentioning
confidence: 99%
“…A single-layer HCG can form a mirrorless high-Q cavity with a Q value as high as 10 7 and emits in surface-normal direction, orthogonal to the periodicity [34,35]. A single HCG itself has been demonstrated as a surface-emitting laser [36]. In addition, HCG has a rich phase response in reflection and transmission, and this promises applications in phase-engineered optics.…”
Section: Introduction To High Contrast Gratingmentioning
confidence: 99%
“…The broadband nature of the HCG has brought many novel features to vertical-cavity surface-emitting lasers (VCSELs) [2][3][4][5][6][7][8][9]. Also, HCG-resonator lasers with surface normal emission have been demonstrated, with properties of interest for sensing, communication, or display applications [10,11]. Extensive theoretical studies of HCGs have revealed that the high index-contrast between the grating and surrounding materials is essential for achieving the extraordinary properties [12].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive theoretical studies of HCGs have revealed that the high index-contrast between the grating and surrounding materials is essential for achieving the extraordinary properties [12]. Thus, all HCG designs reported so far employ low refractive index materials such as air and oxides, for the incident as well as exit medium [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] In addition to the broadband high reflectivity, the reflection/transmission phase of an HCG 6-8 as well as its derivative with respect to the in-plane wavevector 9-11 can be engineered. The control of the derivative of the reflection phase enables it to realize photonic heterostructures in in-plane directions, which is analogous to the electronic quantum wells.…”
mentioning
confidence: 99%